Imbalance of Plasminogen Activator Inhibitor-I/ Tissue Plasminogen Activator and Tissue Factor/Tissue Factor Pathway Inhibitor in Young Japanese Men with Myocardial Infarction - Saigo, Masahiko; Abe, Satoshi; Ogawa, Masakazu; Yamashita, Tsuminori; Biro, Sadatoshi; Minagoe, Shinichi; Maruyama, Ikuro; Tei, Chuwa (Thrombosis and Haemostasis, 2001)
To evaluate the association between haemostatic parameters and increased risk of myocardial infarction (MI) at a young age, we measured fibrinogen, factor VII, antithrombin III, protein C, protein S, tissue factor (TF), free form tissue factor pathway inhibitor (TFPI), plasminogen, 2-antiplasmin, tissue plasminogen activator (tPA), plasminogen activator inhibitor-I (PAI-I), and lipoprotein (a) in 140 young men with MI before age 45 and 150 age-matched healthy men. TF, TF/TFPI ratio, PAI-I, PAI-I/tPA ratio, plasminogen, and lipoprotein (a) in young MI patients were all significantly higher than controls, while TFPI, antithrombin III, and tPA were significantly lower (P <0.001 of each). Significant determinants of MI risk were PAI-I/tPA ratio (R2 = 0.300, P <0.001), TF/TFPI ratio (R2 = 0.049, P <0.001), antithrombin III (R2 = 0.034, P <0.001), hyperlipidaemia (R2 = 0.019, P = 0.004), diabetes (R2 = 0.014, P = 0.015), lipoprotein (a) (R2 = 0.012, P = 0.023), 2-antiplasmin (R2 = 0.014, P = 0.012), and protein C (R2 = 0.012, P = 0.018). We conclude that the imbalances of PAI-I/tPA and TF/TFPI are significantly associated with MI at a young age, perhaps mediated via impaired fibrinolytic activity.
Keywords: Myocardial infarction; age; risk factors; coagulation; fibrinolysis